(NmAGNETIZM KIMBERLITOW I TRAPPOW (B/s - (NtRUHIN(B, (NwLADIMIR iLXI^s; (NvILQEWA(B, (Nw(B.(Na(B.s; (NzIN^UK(B, (Nn(B.(Nn(B.s; (NrOMANOW(B, (Nn(B.(Nn(B.s ((NmOSKWA (B:s (NiZD(B-(NWO mOSK(B. (NUN(B-(NTA(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 147-153 (151 (NNAZW(B.)s
Keywords: (NkIMBERLITY (B((NGEOL(B.)s; (NmAGNITNYE SWOJSTWAs; (NtRAPPYs